Lystrosaurus from Antarctica. American Museum novitates - Colbert, Edwin Harris, 1905- (New York, N.Y. : American Museum of Natural History, 1974)
44 p. : ill., maps 24 cm. Includes bibliographical references (p. 41-44). "The Lower Triassic therapsid reptile Lystrosaurus, first discovered in Antarctica in 1969, is now known from rather abundant materials collected from the Fremouw Formation at Coalsack Bluff, Graphite Peak, and McGregor and Shackleton glaciers, during two field seasons of 1969-1970 and 1970-1971. Two species, L. murrayi and L. curvatus, are identified from portions of skulls, both species having been originally described from South American specimens. The bulk of the Antarctic fossils, consisting of postcranial elements is not specifically identified, but is described and figured. Included are tusks, a stapes, vertebrae, the shoulder girdle and forelimb elements, and the pelvic girdle and hind limb elements. The 31 described species of Lystrosaurus are reviewed, and it is suggested that these probably should be reduced to eight or nine, contained within two evolutionary lines, as propsed by Cluver (1971). These are on the one hand Lystrosaurus curvatus (the most primitive species), L. platyceps, and L. rajurkari, and on the other L. murrayi, L. mccaigi, L. declivis, and L. hedini. Lystrosaurus oviceps may be included with the first of the above-named groups, or it may be an intermediate form. Lystrosaurus weidenreichi, known largely from the postcranial skeleton, is of indeterminate status. The species central to the two lines, L. curvatus and L. murrayi, may represent a primary radiation of the genus through an ancient Gondwanaland. The presence of these two species in Antarctica provides strong evidence for the connection of Antarctica with Africa. Lystrosaurus murrayi in India bolsters the evidence that the Indian peninsula likewise was a part of Gondwanaland. Lystrosaurus murrayi (as well as other species) in China may lend weight to the proposal, advanced by Hurley (1971) and others, that China might have been a portion of the Gondwanaland continent. Alternatively the Chinese forms may have reached eastern Asia by a long ...